Information Technology in the Implementation of Independent Curriculum Based on PJBL in Early Childhood - Karta, I Wayan; Hari Witono; Darmiany; Wiwin Quranita; Hafizzaturroyani (LPPM Undiksha, 2024)
Problems arise mainly in the IT mastery of PAUD teachers, IKM in PAUD and the implementation of PjBL in PAUD. This study aimed to analyse PAUD teachers' ability to use information technology to implement the independent curriculum based on PjBL. This research applies a qualitative descriptive method, using an interview guideline instrument compiled based on aspects of IT mastery, IKM, and implementation of PjBL. The results of the study showed that the ability of PAUD teachers to use information technology in implementing the independent curriculum based on PjBL is categorized as good. The ability of PAUD teachers in the aspect of knowledge using information technology in implementing the independent curriculum based on PjBL is categorized as good and has a positive tendency. The ability of PAUD teachers to use information technology in implementing the independent curriculum based on PjBL is categorized as good but has a slight negative tendency. The ability of PAUD teachers in the aspect of skills in using information technology in implementing the independent curriculum based on PjBL is categorized as good and has a slight negative tendency. The study's conclusion shows that the aspects of knowledge, attitudes, and skills in using information technology have a solid relationship as a hierarchy of competency formation in using information technology in implementing the independent curriculum based on PjBL.